Decreation : The Last Things of All Creatures - Griffiths, Paul J. (Book collections on Project MUSE., 2014)
Death is not the end -- either for humans or for all creatures. But while Christianity has obsessed over the future of humanity, it has neglected the ends for nonhuman animals, inanimate creatures, and angels. In Decreation, Paul J. Griffiths explores how orthodox Christian theology might be developed to include the last things of all creatures. Griffiths employs traditional and historical Christian theology of the last things to create both a grammar and a lexicon for a new eschatology. Griffiths imagines heaven as an endless, repetitively static, communal, and enfleshed adoration of the triune God in which angels, nonhuman animals, and inanimate objects each find a place. Hell becomes a final and irreversible separation from God -- annihilation -- sin's true aim and the last success of the sinner. This grammar, Griffiths suggests, gives Christians new ways to think about the redemption of all things, to imagine relationships with nonhuman creatures, and to live in a world devastated by a double fall.